A pH-sensitive binding modality allows successful transferrin receptor-mediated transcytosis of a bivalent antibody across brain barriers: report - Kuhn, Philipp; Petralla, Sabrina; Dabbagh, Fatemeh; Pegoretti, Valentina; Muranyi, Walter; Ishikawa, Hiroshi; Schroten, Horst; Fischer, Roman; Frenzel, André; Schirrmann, Thomas; Rehm, Markus; Schwerk, Christian; et al. (mAbs, 2025)
Efficient delivery of therapeutics to the central nervous system (CNS) is one of the major challenges in treating neurological diseases due to brain barriers, which prevent entry of almost all potential therapeutic agents into the CNS. Targeting receptors that induce receptor-mediated transcytosis (RMT) across brain barriers has long been heralded as a potential solution to this problem, but this approach has yet to deliver clinical improvements for patients. Here, we set out to identify and characterize bivalent antibodies against the transferrin receptor 1 (TfR) as mediators of RMT. We identified the antibody YU904-F06 (hereafter referred to as F06) that showed efficient transcytosis as a bivalent IgG in two independent in vitro models of brain barriers. Despite its high affinity at extracellular pH levels, we determined that F06’s binding to TfR was greatly reduced at lower pH levels expected during endocytic acidification. We postulated, with the support of a validated predictive mathematical model of RMT, that the pH-sensitivity of F06 allowed it to overcome the lysosomal degradation that has been previously reported for high affinity bivalent binders of TfR. Finally, we demonstrated that F06 could mediate the transcytosis of scFvs that target TREM2 or EGFRvIII as potential therapeutic cargos. In conclusion, we present a proof-of-concept antibody and rationale for the design of high affinity bivalent anti-TfR antibodies that effectively induce RMT by exploiting pH-sensitivity in binding.